a) Đặt \(d=\left(21n+3,6n+4\right)\).
\(\Rightarrow\hept{\begin{cases}21n+3⋮d\\6n+4⋮d\end{cases}}\Rightarrow7\left(6n+4\right)-2\left(21n+3\right)=22⋮d\)
\(\Rightarrow d\in\left\{22,11,2,1\right\}\).
Ta sẽ tìm điều kiện để \(\hept{\begin{cases}21n+3⋮2\\6n+4⋮2\end{cases}}\)và \(\hept{\begin{cases}21n+3⋮11\\6n+4⋮11\end{cases}}\)
- \(\hept{\begin{cases}21n+3⋮2\\6n+4⋮2\end{cases}}\)suy ra \(n\)lẻ.
- \(\hept{\begin{cases}21n+3⋮11\\6n+4⋮11\end{cases}}\)suy ra \(21n+3=22n-n+3⋮11\Leftrightarrow n+8⋮11\Leftrightarrow n=11k-8\left(k\inℤ\right)\).
Với \(n=11k-8\)thì \(6n+4=66k-44⋮11\).
Vậy \(A\)rút gọn được khi \(n\)lẻ hoặc \(n=11k-8\left(k\inℤ\right)\).
b) \(\frac{21n+3}{6n+4}\inℤ\Rightarrow\frac{2\left(21n+3\right)}{6n+4}=\frac{42n+6}{6n+4}=7-\frac{22}{6n+4}\inℤ\Leftrightarrow\frac{22}{6n+4}\inℤ\)
\(\Leftrightarrow6n+4\inƯ\left(22\right)=\left\{-22,-11,-2,-1,1,2,11,22\right\}\)
mà \(n\inℤ\)nên \(n\in\left\{-1,3\right\}\).
Thử lại đều thỏa mãn.